Implementation And Management of A Love-Based Curriculum in Madrasah Ibtidaiyah of Palembang - Basori, Ruchman; Zainuri, Ahmad; Mahendra, Arivan (Journal of Educational Sciences, 2025)
This study explores the management of the Love-Based Curriculum in Madrasah Ibtidaiyah (MI) in Palembang City, focusing on planning, implementation, and evaluation, as well as identifying enabling and inhibiting factors. Using a qualitative descriptive approach, the research involved principals or vice principals for curriculum affairs, teachers, and students. Data were collected through in-depth interviews, participant observation, Focus Group Discussions (FGDs), and document analysis, then analyzed with Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings show that curriculum planning was conducted collaboratively by aligning instructional documents with the official format of the Ministry of Religious Affairs while retaining long-standing positive practices. Implementation emphasized persuasive communication, teachers’ exemplary conduct (uswah hasanah), and participatory methods such as discussions, storytelling, and role-playing to build empathy and cooperation among students. Evaluation combined cognitive and affective dimensions through continuous observation, attitude records, and non-material reinforcement. Enabling factors included strong synergy between family-based and school-based education and the deeply rooted religious culture of Palembang’s community. However, challenges emerged from teachers’ heavy administrative workload and unequal training opportunities, which hindered consistent practice. Overall, the Love-Based Curriculum was effectively applied, offering valuable insights for educators and policymakers in developing humanistic, Islamic value-based learning strategies.